Religion and Crime: Theory, Research, and Practice - Kent R. Kerley (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This volume contains contemporary and cutting-edge research on religion and crime, which includes data-driven (quantitative and qualitative), conceptual, review, and policy-oriented papers.